Expanding sample volume for microscopical detection of nanoplastics - Hiltunen, Arto; Huopalainen, Joona; Mäkilä, Ermei; Häkkilä, Sirkku; Damlin, Pia; Hänninen, Jari (Elsevier BV, 2025)
The extent of nanoplastic pollution has raised severe environmental and health concerns. While the means for microplastic detection are abundant, improved tools for nanoplastic detection are called-for. State-of-the-art microscopic techniques can detect nanoplastics down to tens of nanometers, however, only from small sample sizes (typically ∼ 10 μl). In this work, we describe a method that enables sampling of 1 l of seawater by the means of correlative Raman- and SEM-techniques. This is achieved by adapting common microplastic sample purification protocols to suit the nanoplastic study. In addition, we decorate a membrane filter with SERS-property to amplify the Raman signals. Together, the purification method combined with the use of the SERS-activated-membrane-filter enables identification and imaging of individual nanoplastic particles from significantly larger sample sizes than before. In the nanoscale the average recovery rate is 5 %. These results aim to provide useful tools for researchers in the fight against plastic pollution.